A Note on Unbounded Hyponormal Composition Operators in L2-Spaces - Piotr Budzyński (Journal of Function Spaces and Applications)
We construct an unbounded hyponormal composition operator Cϕ in L2-space such that the domains of Cϕ2 and Cϕ2 are trivial.